Interrelation between fixation asymmetry and gnostic asymmetry in the visual system: what is the leading eye? - N.A. Khokhlov; M.S. Kovyazina; N.V. Vasilevskaya; K.A. Vasilieva (Экспериментальная психология, 2019)
A comparison of the asymmetric visual fixation and the gnostic visual asymmetry was made. The study involved 52 healthy subjects, aged from 15 to 27 years (20.7 ± 2.8), including 18 men and 34 women. To assess the asymmetric fixation a Rozenbakh and an “Aiming” tests were used, to assess the gnostic asymmetry — the authors’ own method was used. It is shown that the fixational eye is not associated with a better perception of the information from the corresponding semi-field of view. However, when adapted to the perceptual task, the role of the ufixational eye increases, and this is more typical for right-eyed people. It was found that in 87% of cases the Rozenbakh test and the “Aiming” test produce the same results when using a two grade evaluation (a “right” and a “left”).